THE EFFECT OF REALITY THERAPY ON THE SEROTONIN LEVEL AND DEPRESSION SCORE IN CERVICAL CANCER PATIENTS - Soetrisno Soetrisno; Supriyadi Hari Respati; Sultoni Emillya Anggraeni; Sri Sulistyowati (Faculty of Medicine, Hasanuddin University., 2017)
ABSTRACT Introduction: Cervical cancer is cancer occurring in the cervix uteri, which is mostly caused by an infection by human papillomavirus (HPV). Women diagnosed with advanced cervical cancer suffer emotional stress that can lead to depression. This condition causes decreasing quality of life, decreasing level of serotonin, and an increase in depression score. Giving reality therapy to patients is expected to have positive effects. Methods: The research was con- ducted through an experiment with pre-test and post-test design. The research samples were15 subjects taken through consecutive sampling from the Polyclinic of Obstetrics and Gynecol- ogy of Dr. Moewardi Hospital Surakarta starting in March 2015. The analysis of serotonin level was conducted in Prodia Laboratory. The experimental data was analyzed using a t-test (α =0.05). Results: The average level of serotonin of the research subjects after receiving reality therapy was higher (223.59 + 41.20) compared to that before the therapy (82.77 + 27.02). From the t-test analysis with p = 0.00, it was found that the average depression score after receiving reality therapy is lower (11:40 + 4.80) compared that before the therapy (17:33 +5:52). Conclusion: There was a significant increase in the serotonin level and a significant decrease in the depression score as the effect of reality therapy given to patients with ad- vanced cervical cancer. Keywords: Serotonin, depression score, reality therapy, advanced cervical cancer